Effect of obesity on rat reproduction and on the development of their adult offspring - Campos, Kleber Eduardo de [UNESP]; Volpato, Gustavo Tadeu [UNESP]; Calderon, Iracema de Mattos Paranhos [UNESP]; Rudge, Marilza Vieira Cunha [UNESP]; Damasceno, Débora Cristina [UNESP] (Associação Brasileira de Divulgação Científica (ABRADIC), 2008)
The aim of the present study was to assess the reproductive parameters of obese Wistar rats and to determine the frequency of their obese adult offspring. Neonatal rats were divided into two groups: F-1 generation, induced to obesity by monosodium glutamate (MSG; F(1)MSG, N = 30), and rats given saline (F1CON, N = 13). At 90 days of age all animals were mated, producing the F-2 offspring (F2CON, N = 28; F(2)MSG, N = 15). Reproductive parameters (fertility, pregnancy, and delivery indexes) were evaluated in F-1 rats. F-2 newborns were weighed, and the obesity parameter for F-1 and F-2 generations was determined from months 5 to 7 of life. At month 7, periovarian fat was weighed and no differences were found. Mean newborn weight also did not differ. The F-1 and F(2)MSG groups presented approximately 90% of obese rats since month 5 of life, whereas F-1 and F2CON groups presented only 33%. There was no difference in periovarian weight among groups. Although obesity did not affect reproductive parameters, obese dams (F(1)MSG) were responsible for the appearance of obesity in the subsequent generation. Thus, obesity induced by neonatal MSG administration did not interfere with reproduction, but did provide a viable model for obesity in second-generation adult Wistar rats. This model might contribute to a better understanding of the pathophysiological mechanisms involved in transgenerational obesity.
Keywords: obesity; offspring; fertility; Wistar rats; monosodium glutamate; transgeneration